Comparison of Infraclavicular and Supraclavicular Brachial Plexus Block in Upper Extremity Surgery - Ayşe Gül Ferlengez; Mustafa Tayfun Aldemir (İstanbul Medical Journal, 2019)

(untitled)
Introduction:In this study, we aimed to compare the efficacy of infraclavicular and supraclavicular brachial plexus block in patients undergoing upper extremity surgery.Methods:After obtaining ethics committee approval, 50 patients who were between the ages of 18-80 years with an “American Society of Anesthesiologists (ASA)” score of I or II and who would undergo elective upper extremity surgery in the orthopedics and traumatology clinic were included in the study. Patients were randomly divided into two groups; 25 patients in infraclavicular block group (group I) and 25 patients in supraclavicular block group (group S). In both groups, nerves were searched using peripheral nerve stimulator and a total of 20 mL of 0.5% levobupivacaine and 20 mL 2% lidocaine were injected into the brachial plexus sheath. Demographic data, ASA scores, operative indications, time to block point, needle depth, onset of block time, operative time, duration of motor and sensory block, and onset of postoperative initial pain were recorded.Results:There was no statistically significant difference regarding the demographic data and operative time between the patients. The time to block point, needle depth and onset of block time were significantly longer in group I than group S (p<0.001, for all). No significant difference was found between the groups in terms of duration of motor block and sensory block, and onset of postoperative initial pain.Conclusion:In our study, we found that the supraclavicular block is more advantageous in terms of time to block point, needle depth and onset of block time.